Direct immunofluorescence study in Thai patients with scleroderma - Kanokvalai Kulthanan (2018)
Objective: Previous reports of direct immunofluorescence (DIF) studies of the skin biopsies in scleroderma were either negative or positive at various percentages and patterns. The present study was designed to evaluate the positive yield and pattern of DIF in Thai patients with scleroderma and its possible clinical correlation. Material and Method: Twenty-two patients with localized or systemic sclerosis, who attended the Department of Dermatology, Siriraj Hospital, from 1996 to 2002, were enrolled in the present study. Skin biopsy was performed for DIF studies. Results: Nine out of 22 patients were diagnosed with systemic sclerosis (SS), eleven with morphea, and two with overlapping syndrome. Fifteen of 22 patients (68%) had positive DIF findings; seven of nine (78%) patients with SS, six of eleven (55%) patients with morphea and two of two (100%) with overlapping syndrome. The common sites of deposit in SS, morphea and overlapping syndrome were dermo-epidermal junction and epidermal nuclei. The common immunoreactant deposit in all groups was IgM. There was no significant difference in the comparison of DIF findings with duration of biopsy lesion, clinical correlation, and the positive result of serum antinuclear antibody (ANA) in the three groups of patients. Conclusion: Positive DIF yield in the present study was higher than previous reports from Western countries. Similar to the study reported from Western country, there was no statistical significant difference in comparison of DIF findings with the duration of lesion, clinical correlation, and the positive result of serum ANA in our three groups of patients. However, patients with SS had a tendency to give more frequently positive ENS and DEJ deposits than those with morphea.